2021
DOI: 10.3389/fimmu.2021.641362
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Circulating T Follicular Helper Cells Induced via IL-12/21 in Patients With Acute on Chronic Hepatitis B Liver Failure

Abstract: ObjectivesT Follicular helper (Tfh) cells, recognized as a distinct CD4+ T cell subset, mediate the development of long-lived humoral immunity via B cell activation/differentiation. Tfh cells play an important role during hepatic viral infection, but its role in hepatitis B virus-related acute on chronic liver failure (HBV-ACLF) remains to be explored.Materials and MethodsThe frequency of Tfh cells, serum pro-inflammatory cytokine (IL-12, IL-21, IL-17 and TNF) levels and IgG/M levels were investigated in HBV-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In the course of natural HBV infection, similar to other proinflammatory cytokines, IL-21 elevates significantly at hepatic flare in AHB, CHB, and HBV-ACLF, especially in those achieving resolve or HBsAg seroconversion subsequently (Chen et al, 2014;Yoshio et al, 2018;Du et al, 2021). IL-21 has a pivotal implication in the instruction of antiviral treatment.…”
Section: Interleukin-21mentioning
confidence: 98%
“…In the course of natural HBV infection, similar to other proinflammatory cytokines, IL-21 elevates significantly at hepatic flare in AHB, CHB, and HBV-ACLF, especially in those achieving resolve or HBsAg seroconversion subsequently (Chen et al, 2014;Yoshio et al, 2018;Du et al, 2021). IL-21 has a pivotal implication in the instruction of antiviral treatment.…”
Section: Interleukin-21mentioning
confidence: 98%
“…Among CD4 + Th cell subsets, naive CD4 + T cells differentiated into Tfh cells can promote humoral immunity by mediating the interaction between T cells and B cells, which are essential for the control of viral infections and vaccine responses (19)(20)(21). Tfh cells, as a novel CD4 + T cell subset, are characterized by the high expression of CXC chemokine receptor 5 (CXCR5), inducible T cell costimulator (ICOS), programmed cell death protein 1 (PD-1), B-cell lymphoma 6 (Bcl-6), and interleukin-21 (IL-21) in both mice and humans and can usually initiate B cells to differentiate into plasma cells that produce high-affinity antibodies to neutralize the virus, such as lymphocytic choriomeningitis virus (LCMV), influenza virus and hepatitis B virus (22)(23)(24)(25). Loss of Tfh cell function can result in primary immunodeficiencies characterized by impaired humoral immunity, including COVID-19 infection, autosomal-dominant hyper IgE caused by STAT3 deficiency and common variable immunodeficiency (21,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 is secreted primarily by macrophages, which are key to initiating the cascade of immune-activated cytokines IFN- γ . Clinical studies have found that serum IL-12 in patients with HBV-ACLF is significantly elevated (approximately 2 times) compared with severe chronic hepatitis B, moderate chronic hepatitis B, and healthy controls [ 57 , 58 ]. IL-12 induces IL-21 through transcription factors STAT1, STAT3, STAT4, and STAT5 [ 59 ] and enhances T follicular helper (Tfh) cells differentiation [ 60 ].…”
Section: Interleukin-12mentioning
confidence: 99%
“…Upregulation of Tfh cells and IL-21 show a close association with the severity/improvement of HBV-ACLF. Serum of patients with HBV-ACLF rich in IL-21 enhances the differentiation of primary CD4 + T cells into Tfh cells, and this interaction can be blocked by anti-IL-21 antibodies [ 57 ]. The production of IL-21 was significantly correlated with the number of Tfh cells, clinical score, and liver function (ALT/AST), verifying the important role of IL-21 in Tfh cell generation during the occurrence of HBV-ACLF [ 57 ].…”
Section: Interleukin-21mentioning
confidence: 99%
See 1 more Smart Citation